2016
DOI: 10.1007/s40572-016-0078-z
|View full text |Cite
|
Sign up to set email alerts
|

Research on Climate and Dengue in Malaysia: A Systematic Review

Abstract: Background & ObjectivesDengue is a climate-sensitive infectious disease. Climate-based dengue early warning may be a simple, low-cost, and effective tool for enhancing surveillance and control. Scientific studies on climate and dengue in local context form the basis for advancing the development of a climate-based early warning system. This study aims to review the current status of scientific studies in climate and dengue and the prospect or challenges of such research on a climate-based dengue early warning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 20 publications
(14 reference statements)
0
51
0
Order By: Relevance
“…another study Ahmad et al (2016a) observed maximum activity of ChE in Anabas testudineus muscles in the range of 25°C to 40°C, while the maximum activity of blood ChE was observed at 30°C. It can be concluded that this particular enzyme works best at temperature ranging from 20°C to 40°C that prevails in Malaysia, a tropical country with warm temperature, high humidity and copious rainfall and average temperature of around 27°C (Hii et al, 2016). The results this study indicate that cadmium induces toxicity on C. gariepinus, and AChE present in the gills of C. gariepinus may serve as a significant biomarker of cadmium induced neurotoxicity.…”
Section: Half Maximal Inhibitory Concentration (Ic50)mentioning
confidence: 65%
“…another study Ahmad et al (2016a) observed maximum activity of ChE in Anabas testudineus muscles in the range of 25°C to 40°C, while the maximum activity of blood ChE was observed at 30°C. It can be concluded that this particular enzyme works best at temperature ranging from 20°C to 40°C that prevails in Malaysia, a tropical country with warm temperature, high humidity and copious rainfall and average temperature of around 27°C (Hii et al, 2016). The results this study indicate that cadmium induces toxicity on C. gariepinus, and AChE present in the gills of C. gariepinus may serve as a significant biomarker of cadmium induced neurotoxicity.…”
Section: Half Maximal Inhibitory Concentration (Ic50)mentioning
confidence: 65%
“…Climatic factors can enhance vector population growth and increase the risk of DENV vectors biting susceptible humans [39][40][41]. Dengue transmission is often seasonal and driven by many climatic factors including temperature, short and long term rainfall and relative humidity influencing mosquito vector growth and density [42][43][44][45].…”
Section: Seasonal and Environmental Factorsmentioning
confidence: 99%
“…Therefore, establishing related risk factors is critical for prediction systems [16]. Given that climate factors play a key role in this disease, identifying the relation between weather information and dengue outbreak incidence is a major task in establishing an accurate prediction system for future outbreaks [17,18,19]. In the current study, important climatic risk factors, such as temperature, relative humidity and rainfall amount, were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid models have been used in outbreak prediction research. A hybrid model is an example of an integrated model, and many models based on genetic algorithms are available to determine the weight in a neural network model [14,17,18,19,25,26]. In Singapore, researchers found signi cant correlated dengue cases with climatic variables by using a Poisson regression model [27].…”
Section: Introductionmentioning
confidence: 99%